2018
DOI: 10.1002/jcb.27906
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐193a‐5p exerts a tumor suppressor role in glioblastoma via modulating NOVA1

Abstract: Background and Objectives Glioblastoma (GBM) is the most common and lethal of intracranial tumors, which is characterized by extensive proliferation and the diffused invasion of tumor cells. MicroRNA‐193a‐5p (miR‐193a‐5p) have been demonstrated previously as a functional suppressor in the development and progression of various cancers. The current study aimed to investigate whether miR‐193a‐5p influences cell proliferation and migration through the mitogen‐activated protein kinase/extracellular signal‐regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…miR-193a-5p has been studied in several tumors and plays a vital role in the post-transcriptional regulation of signaling pathway proteins (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). For example, miR-193a-5p suppressed tumor cell metastasis and epithelial-to-mesenchymal transition by targeting WT1-E-cadherin in non-small-cell lung cancers (41).…”
Section: Discussionmentioning
confidence: 99%
“…miR-193a-5p has been studied in several tumors and plays a vital role in the post-transcriptional regulation of signaling pathway proteins (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). For example, miR-193a-5p suppressed tumor cell metastasis and epithelial-to-mesenchymal transition by targeting WT1-E-cadherin in non-small-cell lung cancers (41).…”
Section: Discussionmentioning
confidence: 99%
“…25 Expression of several miRNAs has been reported to be dysregulated in GBM and to play a significant part in GBM formation and progression. [26][27][28] MiRNAs may perform tumorsuppressive or tumor-promoting functions in GBM through regulation of the expression of their target genes. 29 Hence, elucidation of the functions of cancerassociated miRNAs in GBM may facilitate the identification of promising therapeutic targets in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study also reported an improvement to membranous nephropathy following miR-193a inhibition, which affected podocytosis by targeting WT1 transcription factor (WT1) (28). Jin et al (29) demonstrated that miR-193a-5p exerted a tumor-suppressive role in glioblastoma via modulating NOVA alternative splicing regulator 1. In addition, Shirafkan et al (18) identified that miR-193a-5p inhibited human HT-29 colon cancer cell migration by suppressing the metastatic pathway.…”
Section: Discussionmentioning
confidence: 96%